Type II toxin–antitoxin system, RatAB, contributes to oxidative resistance, biofilm formation and virulence of Edwardsiella piscicida. (3rd February 2022) - Du, Chunmei; Zhang, Wanlin; Gu, Hanjie; Dong, Xiwen; Hu, Yonghua
Abstract: Since the diversity and importance of its role, the type II TA system is attracting increasing attention from researchers. Edwardsiella piscicida is becoming a leading pathogen that threatens seawater and fresh aquaculture, and has been supposed to be a model organism for the study of intracellular infections. Currently, the pathogenesis of E .  piscicida remains unclear, and some new pathogenic factors need to be identified. Type II TA system is largely unknown in E .  piscicida . In this study, a type II TA system, RatAB, was identified and characterized in E .  piscicida . RatA shares high sequence homology with RatA family toxin, and RatB shares high sequence homology with RnfH family protein. rat A and rat B form a bicistronic operon. The biological roles of RatAB were studied by mutants TX01Δ rat A and TX01Δ rat AB, and corresponding complementary strains. The growths of TX01Δ rat A and TX01Δ rat AB were similar to that of TX01 in normal LB medium. However, TX01Δ rat A, especially TX01Δ rat AB, were more sensitive to oxidation pressure than wild strain TX01. Two mutants' abilities to form persistent bacteria were markedly reduced compared with TX01. The deletions of rat A and rat AB reduced bacterial biofilm formation. Cell infection test indicated that the rat A and rat AB mutations damaged E. piscicida ′s ability to adhere and invade host non‐phagocyte and weaken the ability of bacterial to survive and reproduce in host phagocyte. Consistently, in vivo infection tests confirmed that rat A and rat AB were required for bacterial dissemination in host tissues. Taken together, our findings demonstrate for the first time that RatAB is requisite for resistance to adversity and full virulence of E .  piscicida .